Exploring the roles of local food in developing Lenggong Valley as a rural food tourism destination - Abdul Raji, Mohd Nazri; Ab. Karim, Shahrim; Che Ishak, Farah Adibah; Arshad, Mohd Mursyid; Abdul Majid, Mohd Aliff (Universiti Kebangsaan Malaysia Press, 2022)
Integrating the relationship between food and tourism destination has been an important issue in the current tourism scenario. More tourism leaders globally are recognizing the important role local food can play in strengthening a rural destination’s tourism product. Thus, the purpose of this study is to explore the role of local food in developing Lenggong Valley as a rural food tourism destination. This study is applying a qualitative method using in-depth interview and participant observation. The finding identified four steps in developing rural food tourism destination; i) identifying local food components, ii) examining the capabilities of local food as tourism product; iii) evaluating local food as tourism product; and iv) selecting suitable marketing strategy to promote food tourism. This study contributes to expanding research on food tourism in constructing the rural food tourism framework. The information in this study leading to new ways of thinking about local food, by integrating local food and tourism resources to enhance rural destination attraction, since local food at rural destination attract little research in the field of tourism management.